REGIONAL COMPETITIVENESS: THE AGGLOMERATION OF MULTIDIMENSIONAL MODEL IN THE SLEMAN REGENCY OF YOGYAKARTA SPECIAL REGION (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study aim to the building of agglomeration economy in enhancing regional competitiveness by synergize of multidimensional aspect i.e. infrastructure, culture, local endogenous product, technology, regulation, regional set plan, economy and tourism aspect. Research design is mixed method: exploratory and qualitative research by using factor and content analysis. The subject of the research is Sleman Regency of Yogyakarta Special Region, Indonesia. The result of this research can indicate the cluster zoning that proper with the thematic cluster namely agribusiness horticulture and livestock cluster based ecotourism.  When the horticultural and livestock agribusiness cluster based on ecotourism and to collaborate with strategic spatial, it will be gotten the optimum regional development in enhancing regional competitiveness.